EFFECTIVENESS ANALYSIS OF WORK PLANS AND CORPORATE BUDGET PROGRAMS CORPORATE SOCIAL RESPONSIBILITY AND ENVIRONMENT - Salsabila, Ajeng; Karyadi, Karyadi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The budget planned and approved in the company's work plan and budget is the budget that the company will spend for its work program in the future. For this reason, this research aims to determine the effectiveness of the planned budget and its implementation in 2019-2022. The method used in this research is descriptive quantitative, where the nature of the discussion is to describe, compare, and explain the data so that conclusions can be drawn. In the period 2019 to 2022, research results were obtained that showed that the budget and its implementation were almost stable at a "Highly effective" level. This shows the success of company management in implementing the budget according to plan and is a form of corporate responsibility for social and environmental problems. Keywords: Budget; Realization; Effectiveness